Magnitude of anemia and Strategies for Prevention and Control in South East Asia Countries - Kapil, Radhika (Indian Journal of Community Health, 2018)
Anemia is a condition in which the number of red blood cells (and consequently their oxygen-carrying capacity) is insufficient to meet the body’s physiologic needs. Specific physiologic needs vary with a person’s age, gender, residential elevation above sea level (altitude), smoking behavior, and different stages of pregnancy (1). Globally, anemia affects 1.62 billion people (95% CI: 1.50–1.74 billion), which corresponds to 24.8% of the population (95% CI: 22.9–26.7%). The highest prevalence is in preschool-aged children (47.4%, 95% CI: 45.7–49.1), and the lowest prevalence is in adult men (12.7%, 95% CI: 8.6–16.9%). However, the population group with the greatest number of individuals affected is non-pregnant women (468.4 million, 95% CI: 446.2–490.6) (2). The prevalence of anemia is estimated at 9% in countries with high development,in countries with low development, the prevalence is 43% (3).